Permodelan Sistem Informasi Desa Berbasis Web Menggunakan Metode Web Engineering - Aprilianti, Reni (Jurnal Media Borneo, 2024)
Village Information System (SID) is a system designed to facilitate the management of information related to the activities and needs of the community in a village. This system covers various aspects, ranging from village administration, population data, public services, to infrastructure development. The problem of the absence of a village information system includes several aspects that can affect the progress and welfare of people in rural areas. The research objective of web-based village information system modeling using web engineering methods is to develop an information system that can provide support in information management at the village level using web technology. This system is expected to provide easy access for villagers to obtain information related to village administration, public services, and various socio-economic activities that occur in the village. The results of system testing showed a result of 92.4% showing a high success rate in carrying out the functionality and performance of the village information system. The number reflects the level of accuracy and efficiency of the system in meeting user needs and carrying out the desired tasks, this shows that the system has successfully passed the testing stage well and is ready to be implemented more widely.